Impaired dynamic cerebral autoregulation in young adults with mild depression. (29th September 2021) - Zhang, Weijun; Fu, Wen; Yan, Luda; Wang, Mengyu; Ning, Baile; Mo, Xiuyun; Xiong, Li; Liu, Jia; Zhang, Pandeng; Zhong, Jingxin; Sun, Lu; Fu, Wenbin
Abstract: The incidence of depression is increasing, especially in the young adult population. Impaired cognitive function is one of the characteristics of depression, which may be related to impaired cerebral autoregulation (CA). We investigated the characteristics of CA in young adults with mild depression, as well as its validity for identifying patients with depression. Patients (aged 18–35 years) with Hamilton Depression Rating Scale (HAMD) scores ranging from 8 to 17 and a first episode of mild depression were enrolled in this study. Healthy volunteers were recruited as controls. Noninvasive continuous arterial blood pressure and bilateral middle cerebral artery blood flow velocity were simultaneously recorded from each subject. Transfer function analysis was applied to derive phase difference, gain, coherence and rate of recovery for the assessment of CA. Forty‐three patients and 43 healthy controls were enrolled. Phase difference values were significantly compromised in young adults with mild depression and were negatively correlated with HAMD scores. Rate of recovery values estimated from depressed patients was significantly lower. The validity in identifying patients with depression was favorable for the phase difference. The cutoff phase difference value was 29.66. Our findings suggest that dynamic CA was impaired in young patients with mild depression and negatively correlated with HAMD scores. CA represented by phase difference can be used as an objective auxiliary examination of depression, and has clinical diagnostic value for the early identification of patients with depression. Abstract : Cognitive impairment is one of the most common features of depression, which may be related to impaired cerebral autoregulation (CA). The current study, for the first time, investigated the characteristics of CA in young adults with mild depression. The findings suggested that dynamic CA was compromised in young patients with mild depression. CA represented by phase difference has clinical diagnostic value for the early identification of patients with depression.